2007
DOI: 10.1007/s10433-007-0046-4
|View full text |Cite
|
Sign up to set email alerts
|

A possible innovative association between the concept of inter-generational ambivalence and the emotions of guilt and shame in care-giving

Abstract: The present article suggests a tentative new theoretical association between the concept of intergenerational ambivalence and the emotions of guilt and shame in care-giving. The article bases the above suggestion on the paradigm of intergenerational ambivalence as well as on existential and psychological emotion theories dealing with guilt and shame. In certain typical care-giving situations (e.g., leading to institutionalization of the elderly) feelings of guilt can mirror personal-subjective ambivalence (mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 22 publications
1
18
0
5
Order By: Relevance
“…In this way, psychological ambivalence is experienced in relation to—and as a result of—the broader structural contradictions of sociological ambivalence, although few studies have directly addressed the interaction of micro‐level psychological ambivalence and macro‐level sociological ambivalence (Connidis, ). Recent research suggests that intergenerational ambivalence is common in the parent–adult child tie (Peters, Hooker, & Zvonkivoc, ; Rappoport & Lowenstein, ). About 50% of parents report some degree of ambivalence toward their adult children (Fingerman, Hay, & Birditt, ; Pillemer & Suitor, ), and about 30% of adult children experience ambivalence toward their parents (van Gaalen & Dykstra, ; Willson et al, ).…”
Section: Ambivalence In Family Relationshipsmentioning
confidence: 99%
“…In this way, psychological ambivalence is experienced in relation to—and as a result of—the broader structural contradictions of sociological ambivalence, although few studies have directly addressed the interaction of micro‐level psychological ambivalence and macro‐level sociological ambivalence (Connidis, ). Recent research suggests that intergenerational ambivalence is common in the parent–adult child tie (Peters, Hooker, & Zvonkivoc, ; Rappoport & Lowenstein, ). About 50% of parents report some degree of ambivalence toward their adult children (Fingerman, Hay, & Birditt, ; Pillemer & Suitor, ), and about 30% of adult children experience ambivalence toward their parents (van Gaalen & Dykstra, ; Willson et al, ).…”
Section: Ambivalence In Family Relationshipsmentioning
confidence: 99%
“…Van Gaalen and Dykstra (2006) developed a typology of adult child–parent relationships using a large panel study; 29% of families were categorized as ambivalent. Recent qualitative studies have found some degree of intergenerational ambivalence to be present among most or all respondents (Peters, Hooker, & Zvonkovic, 2006; Rappoport & Lowenstein, 2007). Taken together, this set of studies provides strong support for extending the study of ambivalence in intergenerational relations.…”
Section: Ambivalence As An Approach To Understanding Intergenerationamentioning
confidence: 99%
“…This is because empirical analysis has centred predominantly on interpersonal relationships at the expense of broader socio-structural explanations, focusing on the individual, the dyad, or an individual's engagement with others through networks of multiple dyads Katz, 2009;Lowenstein, 2007;Pillemer et al, 2007;Rappoport and Lowenstein, 2007;Ward, 2008;Willson et al, 2003Willson et al, , 2006. Equally, empirical assessment has relied largely on socio-psychological measurements even when the focus of study is potentially of a sociological nature in terms of the normative dimensions of ambivalence (Pillemer and Suitor, 2002: 606-7).…”
Section: Ambivalence and Familymentioning
confidence: 99%